Lives Amid Violence Transforming Development in the Wake of Conflict - Schomerus, Mareike (Bloomsbury Academic, 2022)
Offers original and generalisable conclusions, drawn from comparative global case studies, that challenge the status quo of international development practice in conflict settings.